Cooperative control of multi-agent systems : an optimal and robust perspective /: an optimal and robust perspective. (2020) - Wang, Jianan, 1982-; Wang, Chunyan; Xin, Ming, 1972-; Ding, Zhengtao; Shan, Jiayuan
No abstract available